Guidelines for Sustainable Solid Waste Management of Sawankhalok Municipality, Sawankhalok District, Sukhothai Province - Chumjai, Naiyana; Dokchan, Phasakorn; Wongwatthanaphong, Kampanart (Journal of Graduate MCU KhonKaen Campus, 2025)
This independent study aimed to 1) study the sustainable solid waste management of Sawankhalok Municipality, 2) study the comparison of sustainable solid waste management of Sawankhalok Municipality, classified by personal factors and 3) study the guidelines for sustainable solid waste management of Sawankhalok Municipality. The research was conducted according to the research methodology of combining quantitative research and qualitative research. The population and sample consisted of 371 household representatives in Sawankhalok Municipality and 7 key informants. The research tools were questionnaires and interview forms. Data were analyzed using statistics, frequency, percentage, mean, standard deviation, t-test, F-test, and descriptive data analysis. The research results found that 1) The overall of sustainable solid waste management of Sawankhalok Municipality was at a high level. 2) The comparison of personal factors the research results found that knowledge and understanding of waste separation, types of waste for recycling, and the impact of waste management that were different, the statistical significance level was .05. Therefore, the hypothesis was accepted. 3) The guidelines for sustainable solid waste management of Sawankhalok Municipality found that the every household separated waste according to the 3R principle, promoting and supporting businesses that purchase recycled waste, transform waste, reuse it, and use it as fuel according to the process, establishing a system for collecting hazardous waste from communities, supporting groups to find, research, and develop efficient technologies and issue regulations, rules, and regulations to ensure sustainable waste management